Reliability and validity of an internalizing symptom scale based on the adolescent and adult Semi-Structured Assessment for the Genetics of Alcoholism (SSAGA). (4th March 2019) - Acion, Laura; Kramer, John; Liu, Xiangtao; Chan, Grace; Langbehn, Douglas; Bucholz, Kathleen; McCutcheon, Vivia; Hesselbrock, Victor; Schuckit, Marc; Dick, Danielle; Hesselbrock, Michie; Kuperman, Samuel
ABSTRACT: Background : The Semi-Structured Assessment for the Genetics of Alcoholism (SSAGA) is an interview that assesses psychiatric symptoms and diagnoses, including substance use disorders and anxiety and mood (i.e., internalizing) disorders. Although the SSAGA is widely used, there exists no overall internalizing characteristics scale based on items drawn from SSAGA's mood and anxiety disorder sections. Objectives : To design and assess a SSAGA-based measurement instrument capturing the overall internalizing dimension that underlies more specific internalizing conditions. Methods : We developed, assessed, and characterized a new scale for measuring internalizing problematic characteristics derived from the SSAGA interview. All samples were drawn from the Collaborative Studies on the Genetics of Alcoholism, a prospective multi-site genetic study of families at high risk for alcohol use disorders. All participants taking part in the study between September 2005 and September 2017 were eligible ( n = 904, 52.2% female). Results : The scale had adequate internal consistency (ordinal α = 0.85, 95% CI = [0.81, 0.89]). Construct validity was supported by its association with other measures of internalizing characteristics (Internalizing Scale from Achenbach Self Reports; Neuroticism Scale from the Neuroticism-Extraversion-Openness Five-Factor Personality Inventory). Several indices of alcohol, marijuana, and nicotine misuse were also positively associated with Internalizing Scale scores. Conclusions : The Internalizing Scale has very good psychometric properties and can be used in studies that incorporate the SSAGA interview to study the association between internalizing characteristics and problematic alcohol and other substance use. These associations can potentially be utilized to identify individuals at risk for substance problems and to design treatments targeting such individuals.